The modified gravity light-cone simulation project – I. Statistics of matter and halo distributions. Issue 1 (10th November 2018) - Arnold, Christian; Fosalba, Pablo; Springel, Volker; Puchwein, Ewald; Blot, Linda
ABSTRACT: We introduce a set of four very high resolution cosmological simulations exploring f ( R ) gravity, with 2048 3 particles in 768 and $1536 \, h^{-1} \, {\rm Mpc}$ simulation boxes, for $|\bar{f}_{R0}| = 10^{-5}$ and Λ cold dark matter (ΛCDM), making the set the largest simulations of f ( R ) gravity to date. To mimic real observations, the simulations include a continuous 2D- and 3D-light-cone output dedicated to study lensing and clustering statistics. We present a detailed analysis and resolution study for the matter power spectrum in f ( R ) gravity over a wide range of scales. We also analyse the angular matter power spectrum and lensing convergence on the light-cone. In addition, we investigate the impact of modified gravity on the halo mass function, matter, and halo autocorrelation functions, linear halo bias, and the concentration–mass relation. The impact of f ( R ) gravity is generally larger on smaller scales and smaller redshift. Comparing our simulations to state-of-the-art hydrodynamical simulations, we confirm a degeneracy between f ( R ) gravity and baryonic feedback in the matter power spectrum on small scales, but also find that scales around $k = 1 \, h\, {\rm Mpc}^{-1}$ are promising to distinguish both effects. The lensing convergence power spectrum is increased in f ( R ) gravity. Numerical fits are in good agreement with our simulations for both standard and modified gravity, but tend to overestimate their relative difference on non-linear scales. The halo bias is lower in f ( R ) gravity, whereas halo concentrations are increased for unscreened haloes.